Effect of Information Technology Application Analysis In Marketing Field Activities - Kosdiana Kosdiana Kosdiana (Majalah SIKOMTEK, 2003)
The research aims to analyze PT.Thies increased marketing activities in Indonesia.Observation method was used as a tool for data collection and then processed and analyzedusing data analysis, descriptive.Based on research done by calculating the correlation and regression and testinghipotesis.Dapat known how much influence from more than one independent variables to theoutcome dependen.Maka can know the marketing field and respond to buyers that the productwill be marketed.